Comprehensive Women-centered Treatment for Substance Use Disorders in Georgia: Current Status and Future Directions - Otiashvili, David (J Subst Use, 2014)
The present paper examines the current status of women-centered substance use disorder treatment in Georgia. Four major issues are identified that adversely impact the delivery of effective services for women with substance use disorders: Policy Issues; Sociocultural Issues; Programmatic/Structural Issues; and Personal/Interpersonal Issues. These four issues are seen to form a complex, dynamic system that serves to maintain the current ineffective service delivery system and suppresses movement toward an effective service delivery for this highly marginalized and at-risk population. How these issues, and their interplay, present continuing barriers to the development and implementation of effective treatment for this population are outlined and discussed. In order to overcome these barriers, solutions must be sought in four areas: Policy reform; Public health campaigns; Development and implementation of comprehensive women-specific confidential treatment models; and Empowering women. Specific goals in each of these areas that would achieve a positive impact on various aspects of the functioning of the current service delivery system for women with substance use disorders are suggested. Simultaneously seeking solutions in all four of these areas would improve the service delivery system and benefits women with substance use disorders.